INTEGRASI KEILMUAN PESANTREN (Studi Korelasi Antara Ilmu Agama dan Ilmu Umum di Institut Ilmu Keislaman Annuqayah) - QADARIYAH, LAILATUL; SUBHAN, MOH (Fakultas Agama Islam Universitas Islam Madura, 2019)
Integration of science is a combination of separate sciences into a cohesion of knowledge, in this case the unification between the sciences that are religious in nature and the sciences that are general in nature. Integration of religion and general science is an effort to merge polarism between the science of religion and science which results from the mindset between religious sciences as an independent source of truth and science as an independent source. The concept of integration of religious science and general science in INSTIKA is inseparable from the basic values (qiyamusiaanyah) that are embedded in every step and educational activity carried out in it. The Islamic Institute of Annuqayah cults itself as a campus of manners, manners are an acronym for Takwa, Tafaqquh, Khidmah and rahmatan lil alamin. The three basic values of INSTICS are summarized from QS. At-Taubah verse 122. The rahmatan lil „alamin is a universal value that encompasses the three basic values which function to underlie, integrate and direct their orientation. Application of the curriculum in INSTIKA there is no separation between religious science and general science. In terms of concepts, religion and general science are taught in lecture sessions at INSTIKA, such as tasawuf, logic or mantiq lecture material, philosophy, interpretation, science and so on, all organized in curriculum units according to each study program. in INSTIKA.